Phytochemical screening and antioxidant properties of methanolic extract of root of Asparagus racemosus Linn. Issue 1 (1st January 2018) - Behera, Suraj Kumar
ABSTRACT: This study was to carry out phytochemical screening, to determine the total phenolic and flavonoid content as well as to evaluate the antioxidant properties of methanolic extract of root of Asparagus racemosus . Antioxidant properties were determined by 1, 1- diphenyl, 2-picrylhydrazyl (DPPH), hydroxyl radical, superoxide radical, hydrogen peroxide assay and total antioxidant activity by the phosphomolybdenum assay. The result showed that the powdered roots of A. racemosus were extracted with methanol and the percentage of yield was 29.2%. The total phenolic and flavonoid contents of the extracts were 12.90 ± 0.002 mg/g and 0.80 ± 0.001 mg/g dry weight respectively. The plant sample possesses high free radical scavenging activity and phytochemical constituents which might be useful for further studies to fight against oxidative stress.